RESTRIÇÃO ALIMENTAR E REALIMENTAÇÃO DE PACUS Piaractus mesopotamicus EM DIFERENTES FASES DE PRODUÇÃO - RUBIA MARA GOMES (2025)
Feeding strategies, such as feed restriction followed by refeeding, have proven effective in fish, inducing compensatory growth, improving feed utilization, and preserving water quality. Systems like recirculating aquaculture systems (RAS) and net cages provide ideal conditions for implementing these practices, promoting sustainability, cost reduction, and improved aquaculture performance. This study evaluated the application of feed restriction cycles (15 days) followed by refeeding (15 days) in pacu (Piaractus mesopotamicus) during juvenile and finishing phases in closed (RAS) and open (net-cage) systems, analyzing productive, physiological, nutritional, and metabolic aspects, lipid profile, and economic viability. In Chapter 2, pacu subjected to feed restriction and refeeding cycles showed significant differences in zootechnical performance, morphological indices, and body composition. While continuously fed fish exhibited greater weight and growth, those under restriction showed better results in crude protein, mineral matter, and certain fatty acids. Efficient energy reserve mobilization was evident, but no irreversible damage to hepatic and intestinal tissues was observed, with partial recovery after refeeding, indicating the species' metabolic resilience. In Chapter 3, conducted on a farm with net cages, the control group showed higher weight gain and feed intake, while other performance parameters did not show significant differences (P>0.05), indicating partial compensatory growth. Fish subjected to feed restriction showed increased amylase enzyme activity, triglycerides (+68.36%), crude protein, and essential omega-3 and omega-6 fatty acids. Physiological indices suggested metabolic and digestive adaptation without compromising zootechnical performance or fish health. The feed restriction and refeeding strategy was effective and sustainable in the grow-out phase in net cages, standing out as a viable management technique depending on the production phase and cultivation system used. In Chapter 4, RAS production with a stocking density of 50 fish/m³ was economically unviable. However, with 100 fish/m³, feed restriction proved viable in the short term. Net-cage production demonstrated economic feasibility in both feeding strategies. The SR treatment yielded a profit of R$ 557.37, while the CR treatment was more profitable, generating R$ 1,274.19. Feed restriction followed by refeeding can be a viable strategy for aquaculture, promoting production efficiency and sustainability. The metabolic adaptation of pacus without health impairments reinforces its application potential. Economic viability depends on stocking density and the cultivation system adopted.